PENGARUH OPERATING LEVERAGE, ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) TERHADAP RETURN ON ASSET PADA PT. SEPATU BATA TBK. PERIODE 2011-2018: accounting & finance - Asep Suryana, SE., M.AK (P3M STIE PASIM Sukabumi, 2018)
The use of fixed assets in a company will make the company bear fixed costs (operating leverage) every period. This operating leverage decision will affect the Return On Assets of a company. Where the Return On Assets of the company is used by investors to see the extent to which the company can generate profits from the assets they have. Based on this, the authors give the title of this study, namely: